Labor migration and its impact on human dignity: A problem of the migrant worker - Torres Cadillo, Rosa Isabel (2022)
Migration is a permanent problem not only for foreigners, but also for the destination country, because the migrant represents a person in search of work and opportunities, who often, by necessity, opts for any kind of (precarious) work, even with a derisory remuneration. This situation is compounded by the stigmatization and discrimination of migrant workers, due to their status, which has a negative impact on their dignity, as they are often humiliated, insulted and abused. This is the daily reality of migrant workers in our country.